RARE-EARTH ELEMENTS IN TRAP ROCKS OF ANCIENT PLATFORMS - Al'mukhamedov A.I.; Zolotukhin V.V.; Smirnova Ye.V.; Konusova V.V.; Chuvashova L.A. (My University, 1989)
Basalt flows which cover ancient platforms and are part of trap formations are typical examples of continental intraplate magmatism. In recent years, they have attracted a great deal of attention from investigators, because of their wide occurence and their geochemical difference from the basalt of the midocean ridges, despite similar general composition. Two main model relate to differences in the PT conditions of melting and subsequent differentiation of parent magmas, and disparities in the composition of the upper mantle under the oceans and continents. According to the data the dominant source of the rare earth elements was the upper mantle, probably less depleted than mantle of the oceans. Regional variations in the composition of the mantle substrate also are likely.